Spatial Assessment of the Conformity Between Educational Facility Needs and Provision in Surakarta City Based on SNI Standards, 2004–2024 - Putri, Elza Henvita; Werdiningtyas, Rr. Ratri; Widodo, Candraningratri Ekaputri (Indonesian Journal Publisher, 2025)
Surakarta City, as one of the strategic service centers in Central Java Province, is facing challenges in realizing equal distribution of educational facilities by the Indonesian National Standard (SNI). This study aims to evaluate existing conditions, gaps in needs, and the level of conformity between the provision of educational facilities and applicable standards. The approaches used include quantitative descriptive methods, spatial analysis, buffering techniques, Average Nearest Neighbor Analysis (ANN), Kernel Density Estimation (KDE), and descriptive qualitative analysis. The findings show a striking inequality in the distribution of educational facilities between regions, with a higher concentration of facilities in the city center compared to the outskirts. Through ANN and KDE analysis, it was found that the distribution pattern of educational facilities varies, from clustered, random, to scattered patterns, depending on the level of education. The shortage of facilities was recorded at the elementary school level of 140 units, junior high schools 49 units, and senior high schools/vocational schools 41 units. Based on these results, it is recommended that a strategy be developed to distribute educational facilities more evenly, considering spatial needs and demographic dynamics. This finding is an important foundation in planning sustainable education based on a spatial approach in Surakarta City.